Insomnia and Neurocognitive Functioning in Adult Survivors of Childhood Cancer. Issue 3 (19th February 2020) - Tonning Olsson, Ingrid; Lubas, Margaret M; Li, Chenghong; Mandrell, Belinda N; Banerjee, Pia; Howell, Carrie R; Ness, Kirsten K; Srivastava, Deokumar; Robison, Leslie L; Hudson, Melissa M; Krull, Kevin R; Brinkman, Tara M
Abstract: Background: In noncancer populations, insomnia is known to affect neurocognitive processes. Although the prevalence of insomnia appears to be elevated in survivors of childhood cancer, relatively little is known about its association with neurocognitive performance in this at-risk population. Methods: A total of 911 survivors (51.9% female; mean [SD] age, 34 [9.0] years; time since diagnosis, 26 [9.1] years) completed direct assessments of attention, memory, processing speed, and executive functioning and self-reported symptoms of sleep (Pittsburgh Sleep Quality Index), fatigue (Functional Assessment of Chronic Illness Therapy-Fatigue), and daytime sleepiness (Epworth Sleepiness Scale). Sex-stratified general linear models were used to examine associations between insomnia and neurocognitive performance, with adjustment for treatment exposures and chronic health conditions. All statistical tests were two-sided. Results: Insomnia was reported by 22.1% of females and 12.3% of males ( P  < .001). After adjustment for neurotoxic treatment exposures, insomnia (vs healthy sleepers with no daytime fatigue or sleepiness) was associated with worse neurocognitive performance in the domains of verbal reasoning, memory, attention, executive function, and processing speed (verbal reasoning: males β = −0.34, P  = .04, females β = −0.57, P  < .001; long-term memory: males β = −0.60, P  < .001, females β = −0.36, P  = .02; sustained attention: males β = −0.85, P  < .001, females β = −0.42, P  = .006; cognitive flexibility: males β = −0.70, P  =   .002, females β = −0.40, P  = .02). Self-reported sleep disturbance without daytime fatigue or sleepiness or daytime fatigue or sleepiness alone were not consistently associated with poorer neurocognitive performance. Conclusions: Insomnia was highly prevalent and contributed to the neurocognitive burden experienced by adult survivors of childhood cancer. Treatment of insomnia may improve neurocognitive problems in survivors.